Real Time Monitoring System for Peat Soil - Lim, She Ley; Shipun Anuar Hamzah (Evolution in Electrical and Electronic Engineering, 2023)
This work is about real-time monitoring of peat soil temperature and humidity based on Internet of Things (IoT) technology. Fires in peatland forests often occur, especially during hot weather, and it takes a long time to put them out. This is because the fire spreads on the surface and in the peat soil, making it difficult to extinguish. However, most researchers have developed a forest fire monitoring system by measuring the temperature in the surrounding area or on the peat surface. This results in inaccurate temperature and humidity readings of the peat soil. Hence, soil bottom temperature and humidity readings are important and need to be obtained immediately to prevent fires. In this work, a bucket height of 30 cm and a volume of 18 liters are used, filled with peat soil. Temperature and humidity sensors are placed in three positions: sensor 1 (surrounding the soil), sensor 2 (soil surface), and sensor 3 (soil bottom). The system is tested and placed outside the building. Data is collected at 10 am, 12 pm, and 3 pm each day. Based on the results from day one, the temperature of the surrounding sensor has an average value of 30.5°C, the soil surface is 29.7°C, and the soil bottom is 28.7°C. The humidity of the surrounding sensor has an average percentage of 69.1%, the soil surface is 91.1%, and the soil bottom is 96.7%. The average temperature and humidity results show a correlation between the humidity and temperature of the soil. When the temperature is hot, the humidity decreases, which is observed in all three sensors. For monitoring purposes, this system is equipped with message notifications connected to the Telegram channel. The average reading of these sensors is set to low temperature (reading < 20°C), medium temperature (reading 21°C-36°C), and hot temperature (reading 37°C and above). Referring to day one, the average soil temperature indicates that the soil condition is moderate.